Partial annular pancreas in a 12-year-old girl - Savić, Djordje; Prokić, Dragan; Grujić, Blagoje; Vukadin, Miroslav; Milojković Marinović, Vesna; Rašić, Petar; Miličković, Maja (Vojnosanitetski pregled, 2022)
Introduction. Annular pancreas is a rare congenital anomaly in which a band of the pancreatic tissue, in continuity with the pancreatic head, completely or incompletely surrounds the descending part of the duodenum. An abnormal pancreatic development can cause complete annular pancreas, partial annular pancreas, and pancreas divisum. Complete annular pancreas is diagnosed in newborns, while the diagnosis of the partial annular pancreas is more frequently established in adults. The most reliable diagnostic methods are computed tomography and magnetic resonance cholangiopancreatography. The anomaly is treated surgically, using bypass procedures. Case report. A 12-year-old girl presented malnourished, with occasional feeding problems, vomiting, heartburn, and pain from infancy. The upper gastrointestinal series showed an extremely dilated stomach, the first and the second part of the duodenum. An endoscopic exam revealed the dilated stomach, pylorus, and the first and the second part of the duodenum with retained contrast, while the entrance of the endoscope into the third part of the duodenum was not possible. Computed tomography showed pancreatic tissue encircling the second part of the duodenum and the characteristic "crocodile jaw" sign. Roux-en-Y duodenojejunostomy was performed as a bypass procedure. Conclusion. The complete annular pancreas is a well-known and easily diagnosed anomaly in newborns. The partial annular pancreas is often poorly recognized, especially in patients who do not present with marked duodenal obstruction. Unrevealed, it causes chronic problems in food intake, with possible serious complications. Although a very rare condition in the pediatric population, partial annular pancreas should be taken into consideration in unclear cases of chronic poor oral food intake and vomiting.
Keywords: annular pancreas; child; diagnosis; endoscopy, digestive system; tomography, x-ray computed.